Urinary tract infection caused by community-acquired extended-spectrum β-lactamase-producing bacteria in infants - Yun Hee Kim; Eun Mi Yang; Chan Jong Kim (Elsevier, 2017)
Objective: Urinary tract infection (UTI) caused by resistant strains of bacteria is increasingly prevalent in children. The aim of this study was to investigate the clinical characteristics and risk factors for UTI caused by community-acquired extended-spectrum β-lactamase (CA-ESBL)-producing bacteria in infants. Methods: This was a retrospective study performed over 5 years in a single Korean center. Hospitalized infants with febrile UTI were enrolled and divided into two groups (CA-ESBL vs. CA non-ESBL UTI). The yearly prevalence was calculated. Baseline characteristics and clinical course such as fever duration, laboratory and radiological findings were compared between the two groups. Risk factors associated with the CA-ESBL UTI were investigated. Results: Among the enrolled infants (n = 185), 31 (17%) had CA-ESBL UTI. The yearly prevalence of ESBL of CA-ESBL UTI increased during the study (0% in 2010, 22.2% in 2015). Infants with CA-ESBL UTI had a longer duration of fever after initiating antibiotics (2.0 ± 1.1 vs. 1.5 ± 0.6 days, p = 0.020). Cortical defects on renal scan and early treatment failure were more frequent in CA-ESBL (64.5 vs. 42.2%, p = 0.023; 22.6 vs. 4.5%, p = 0.001). A logistic regression analysis revealed that urinary tract abnormalities and previous UTI were independent risk factors for CA-EBSL UTI (odds ratio, 2.7; p = 0.025; 10.3; p = 0.022). Conclusion: The incidence of UTI caused by ESBL-producing bacteria has increased in Korean infants. Recognition of the clinical course and risk factors for ESLB-producing UTI may help to determine appropriate guidelines for its management. Resumo: Objetivo: A infecção do trato urinário (ITU) causada por cepas de bactérias resistentes está cada vez mais prevalente em crianças. O objetivo deste estudo foi investigar as características clínicas e os fatores de risco de ITU causada por bactérias produtoras de β-lactamases de espectro ampliado adquiridas na comunidade (ESBL CA) em neonatos. Métodos: Este foi um estudo retrospectivo realizado por mais de 5 anos em um único centro coreano. Neonatos internados com ITU febril foram inscritos e divididos em dois grupos (ITU por ESBL CA em comparação a não ESBL CA). A prevalência anual foi calculada. As características básicas e o curso clínico, como duração da febre e achados laboratoriais e radiológicos, foram comparados entre os dois grupos. Os fatores de risco associados à ITU por ESBL CA foram investigados. Resultados: Entre os neonatos inscritos (n = 185), 31 (17%) apresentaram ITU por ESBL CA. A prevalência anual de ESBL em ITU por ESBL CA aumentou durante o estudo (0% em 2010, 22,2% em 2015). Os neonatos com ITU por ESBL CA apresentaram maior duração de febre após o início dos antibióticos (2,0 ± 1,1 em comparação a 1,5 ± 0,6 dias, p = 0,020). Os defeitos corticais no exame renal e a falha precoce no tratamento foram mais frequentes em ESBL CA (64,5 em comparação a 42,2%, p = 0,023; 22,6 em comparação a 4,5%, p = 0,001). Uma análise de regressão logística revelou que as anomalias do trato urinário e a ITU anterior eram fatores de risco independentes de ITU por ESBL CA (razão de chance: 2,7; p = 0,025; 10,3; p = 0,022). Conclusão: A incidência de ITU causada por bactérias produtoras de ESBL aumentou em neonatos coreanos. O reconhecimento do curso clínico e dos fatores de risco de ITU por ESBL poderá ajudar a determinar as diretrizes adequadas de manejo. Keywords: Urinary tract infection, Antimicrobial resistance, β-Lactamase, Risk factors, Infant, Palavras-chave: Infecção do trato urinário, Resistência antimicrobiana, β-Lactamase, Fatores de risco, Neonato